The independent prognostic effect of marital status on non-small cell lung cancer patients: a population-based study - Zhao, Dechang; Zhang, Rusi; Yang, Longjun; Huang, Zirui; Lin, Yongbin; Wen, Yingsheng; Wang, Gongming; Guo, Guangran; Zhang, Lanjun (Frontiers in Medicine, 2023)
Background: Previous studies had demonstrated that marital status was an independent prognostic factor in multiple cancers. However, the impact of marital status on non-small cell lung cancer (NSCLC) patients was still highly controversial. Method: All NSCLC patients diagnosed between 2010-2016 were selected from the surveillance, epidemiology and end results (SEER) database. To control the confounding effect of related clinicopathological characteristics, propensity score matching (PSM) was conducted between married and unmarried groups. In addition, independent prognostic clinicopathological factors were evaluated via Cox proportional hazard regression. Moreover, nomograms were established based on the clinicopathological characteristics, and the predictive accuracy was assessed by calibration curves. Furthermore, decision curve analysis (DCA) was used to determine the clinical benefits. Results: In total, 58424 NSCLC patients were enrolled according to the selection criteria. After PSM, 20148 patients were selected into each group for further analysis. The married group consistently demonstrated significantly better OS and CSS compared to unmarried group (OS median survival (95% CI): 25 (24-26) vs. 22 (21-23) months, P<0.001; CSS median survival (95% CI): 31(30-32) vs. 27(26-28) months, P<0.001). Moreover, single patients were associated with the worst OS (median survival (95% CI): 20 (19-22) months) and CSS (median survival (95%CI): 24(23-25) months) among unmarried subgroups. Besides, unmarried patients had a significantly worse prognosis compared to married patients in both univariate and multivariate Cox proportional hazard regressions. Furthermore, married group was associated with better survival in most subgroups. To predict the 1-, 3- and 5-year OS and CSS probabilities, nomograms were established based on age, race, sex, gender, marital status, histology, grade, TNM stage. The C-index for OS and CSS were 0.759 and 0.779. And the calibration curves showed significant agreement between predictive risk and the observed probability. DCA indicated nomograms had consistently better predict performance. Conclusion: This study demonstrated that unmarried NSCLC patients were associated with significantly worse OS and CSS compared to married NSCLC patients. Therefore, unmarried patients need not only closer surveillance, but also more social and family support, which may improve patients’ adherence and compliance, and eventually improve the survival.